Spin crossover and valence tautomerism conductors - Wang, Min; Li, Zhao-Yang; Ishikawa, Ryuta; Yamashita, Masahiro (Coordination chemistry reviews, 2021)
•Spin crossover (SCO) and valence tautomerism (VT) conductors are summarized.•Magnetic properties and conductivities of SCO and VT conductors are discussed.•Synergistic and cooperative properties of bistability and conductivity are presented. Multifunctional molecular materials exhibiting both magnetic bistability and electrical conductivity have excellent application potential in microelectronic devices. In the last two decades, research into conductive magnets and switching materials has continuously expanded and provided materials with practical application prospects. In this review, we present the recent progress on spin crossover and valence tautomerism conductors, focusing on syntheses, strategies, crystal structures, magnetic properties, and conductivities of such materials as well as synergistic and cooperative properties of bistability and conductivity.